1989
DOI: 10.1104/pp.89.2.664
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation, and Intracellular Localization of a 33-kD Cationic Peroxidase in Excised Cucumber Cotyledons

Abstract: Ethylene enhanced chlorosis and levels of 33-kilodalton cationic peroxidase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…Levels of pI 9 and pI 4 peroxidase isolated from acetone powders of seedling tissue were measured using an RID assay described earlier (2). Acetone powders of cotyledons were used to measure the peroxidases from various species of Cucurbitaceae.…”
Section: Peroxidase Assaymentioning
confidence: 99%
“…Levels of pI 9 and pI 4 peroxidase isolated from acetone powders of seedling tissue were measured using an RID assay described earlier (2). Acetone powders of cotyledons were used to measure the peroxidases from various species of Cucurbitaceae.…”
Section: Peroxidase Assaymentioning
confidence: 99%
“…Saunders and McClure (1976) reported that many kinds of flavonoid are present in the chloroplast of many species of vascular plants. Peroxidase activity was also found in the chloroplasts of spinach leaves (Takahama, 1984), cucumber cotyledons (Abeles et al, 1989) and barley leaves (Kuroda et al, 1990). Huff (1982) demonstrated that Chl derivatives, chlorophyllide and pheophytin, as well as…”
Section: Chlorophyll Degradation Productsmentioning
confidence: 95%
“…It clearly implies that ICL and SAG 281 gene are involved in cotyledon senescence at the point of chloroplast (or chlorophyll) destruction together with other senescence-related enzyme coding gene's action such as various plant peroxidases [1,8,10,16,26,34]. As discussed in earlier section, Cs1-MMP may be responsible for closing the death of a cell [43].…”
Section: One Of the Cysteine Biosynthesis Involving Sag 3-5mentioning
confidence: 99%
“…From earlier senescence study in cucumber, a plant peroxidase (33-CPO) activity was promoted by ABA and JA as ethylene but was retarded by IAA, GA and kinetin from excised cotyledon [1]. They also showed induction of the peroxidase isoenzymes by both ethylene and JA following induced senescence in cucumber cotyledon.…”
Section: One Of the Cysteine Biosynthesis Involving Sag 3-5mentioning
confidence: 99%
See 1 more Smart Citation